Metal-induced neurodegeneration in C. elegans - Aschner, Michael; Chen, Pan; Martinez-Finley, Ebany J.; Bornhorst, Julia; Chakraborty, Sudipta (Frontiers in Aging Neuroscience, 2013)
The model species, Caenorhabditis elegans (C. elegans), has been used to probe for mechanisms underlying numerous neurodegenerative diseases. C. elegans are particularly amenable to the study of neurodegeneration as the entire genome has been mapped and consists of 302 neurons, and 5,000 synapses. Neuronal subtypes can be fluorescently labeled allowing for in vivo imaging. The ease of genetic manipulation in this model system is also particularly alluring. Notably, C. elegans share 60-80% homology with human genes and contain genes involved in metal homeostasis and transport, allowing for the study of metal-induced degeneration in the nematode. This review will discuss the C. elegans model with emphasis on metal-induced neurodegeneration and a focus on mechanisms associated with neurodegenerative and neuroprotective processes within the context of gene x environment interactions.